Factors Affecting the Work Efficacy of Employees of Automotive Parts Factories at Chonburi Province: Factors affecting the work efficacy of employees of automotive parts factories at Chonburi province. - Srirom, Namfon; Changchai, Nuttawee; Sirijaroonwong, Umarat (Journal of Health Sciences and Wellness, 2020)
The objectives of this study were to evaluate employees’ opinions about work efficiency, to identify the difference in performance between gender and to study the relationship between health threat factors from the working environment and the work efficiency of the employees. It was a cross-sectional descriptive study. Sixty seven (67) samples were selected in this study and the questionnaire was used to collect the data. Data analysis was undertaken by using the independent T-test and Pearson correlation. The result indicated that the majority of sample in the study was male. Most of them were between 23-35 years old, with academic qualification level below bachelor degree. Duration of working at the company was 10-17 years. Mainly, monthly income was between 9,000 to 26,000 baht. Sample has the opportunity level of exposure to health hazards from the work environment as perceived by employees in overall, was at a medium level (mean = 2.97 ±.80) with the highest opportunity of exposure to physical health hazards (mean = 3.22 ±.97). The top three aspects regularly exposed were the loud noise, hot working atmospheres and heat from the machines (37.50 35.80 and 28.40 % respectively). On the other hand, the efficacy of work according to the opinion of employees was at a high level (mean = 3.97 ±.56). Males had significantly higher levels of working efficiency than females (p = 0.004). The opportunities for exposure to biological and psychosocial hazards had significantly significant correlation with the efficacy level of working (p =0.01 and 0.02 respectively). However, the correlations were positively correlated at quite low levels (r = 0.31 and 0.27 respectively).